Specific combination of compound heterozygous mutations in 17β-hydroxysteroid dehydrogenase type 4 (HSD17B4) defines a new subtype of D-bifunctional protein deficiency - McMillan, Hugh J; Worthylake, Thea; Schwartzentruber, Jeremy; Gottlieb, Chloe C; Lawrence, Sarah E; MacKenzie, Alex; Beaulieu, Chandree L; Mooyer, Petra A W; Wanders, Ronald J A; Majewski, Jacek; Bulman, Dennis E; Geraghty, Michael T; et al. (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background D-bifunctional protein (DBP) deficiency is typically apparent within the first month of life with most infants demonstrating hypotonia, psychomotor delay and seizures. Few children survive beyond two years of age. Among patients with prolonged survival all demonstrate severe gross motor delay, absent language development, and severe hearing and visual impairment. DBP contains three catalytically active domains; an N-terminal dehydrogenase, a central hydratase and a C-terminal sterol carrier protein-2-like domain. Three subtypes of the disease are identified based upon the domain affected; DBP type I results from a combined deficiency of dehydrogenase and hydratase activity; DBP type II from isolated hydratase deficiency and DBP type III from isolated dehydrogenase deficiency. Here we report two brothers (16½ and 14 years old) with DBP deficiency characterized by normal early childhood followed by sensorineural hearing loss, progressive cerebellar and sensory ataxia and subclinical retinitis pigmentosa. Methods and results Biochemical analysis revealed normal levels of plasma VLCFA, phytanic acid and pristanic acid, and normal bile acids in urine; based on these results no diagnosis was made. Exome analysis was performed using the Agilent SureSelect 50Mb All Exon Kit and the Illumina HiSeq 2000 next-generation-sequencing (NGS) platform. Compound heterozygous mutations were identified by exome sequencing and confirmed by Sanger sequencing within the dehydrogenase domain (c.101C>T; p.Ala34Val) and hydratase domain (c.1547T>C; p.Ile516Thr) of the 17β-hydroxysteroid dehydrogenase type 4 gene (HSD17B4). These mutations have been previously reported in patients with severe-forms of DBP deficiency, however each mutation was reported in combination with another mutation affecting the same domain. Subsequent studies in fibroblasts revealed normal VLCFA levels, normal C26:0 but reduced pristanic acid beta-oxidation activity. Both DBP hydratase and dehydrogenase activity were markedly decreased but detectable. Conclusions We propose that the DBP phenotype seen in this family represents a distinct and novel subtype of DBP deficiency, which we have termed type IV based on the presence of a missense mutation in each of the domains of DBP resulting in markedly reduced but detectable hydratase and dehydrogenase activity of DBP. Given that the biochemical testing in plasma was normal in these patients, this is likely an underdiagnosed form of DBP deficiency.